2020
DOI: 10.21203/rs.3.rs-54834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA CBR3-AS1 Regulates of Breast Cancer Drug Sensitivity as a Competing Endogenous RNA Through the JNK1/MEK4‑Mediated MAPK Signal Pathway

Abstract: Background: Adriamycin (ADR) resistance is one of the main obstacles to improve the clinical prognosis of breast cancer (BRCA) patients. Long non-coding RNAs (lncRNAs) can regulate cell behavior, but the role of these RNAs in anti ADR of BRCA remains unclear. Here we aim to investigate the imbalance of a particular long noncoding RNA, lncRNA CBR3 antisense RNA 1 (CBR3-AS1), and its role in ADR resistance.Methods: Microarray analysis of ADR-resistant BRCA cells was performed to identify CBR3-AS1. CCK8 assay and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…[136][137][138][139] c-Jun N-Terminal Protein Kinase 1 (JNK1; encoded by MAPK8) regulates the survival, apoptosis, metastasis, and inflammation of ERPBC cells, and it also mediates the pharmacological effects of anticancer drugs. [140][141][142][143][144][145] Malfunction and loss-of-function polymorphisms of TP53 induce the development and progression of ERPBC, and the expression and mutation status of this gene are correlated with the survival and prognostic outcomes of BC patients. 77,[146][147][148][149][150][151][152][153][154] Vascular endothelial growth factor (VEGF)-A (encoded by VEGFA) may contribute to the metastasis, angiogenesis, growth, and drug resistance of ERPBC cells, 89,[155][156][157] and its expression level and polymorphisms may act as genetic markers for the risk, progression and recurrence, clinical outcomes for endocrine and antiangiogenic therapies, and survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[136][137][138][139] c-Jun N-Terminal Protein Kinase 1 (JNK1; encoded by MAPK8) regulates the survival, apoptosis, metastasis, and inflammation of ERPBC cells, and it also mediates the pharmacological effects of anticancer drugs. [140][141][142][143][144][145] Malfunction and loss-of-function polymorphisms of TP53 induce the development and progression of ERPBC, and the expression and mutation status of this gene are correlated with the survival and prognostic outcomes of BC patients. 77,[146][147][148][149][150][151][152][153][154] Vascular endothelial growth factor (VEGF)-A (encoded by VEGFA) may contribute to the metastasis, angiogenesis, growth, and drug resistance of ERPBC cells, 89,[155][156][157] and its expression level and polymorphisms may act as genetic markers for the risk, progression and recurrence, clinical outcomes for endocrine and antiangiogenic therapies, and survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The natural log value of the fitted half-maximal inhibitory concentration [LN(IC50)] of each drug was adopted to select caner-associated drugs which were specifically sensitive to mutant subtypes (C1 and C2). Many attempts have been made to perform in vitro pharmacogenomic response analyses based on the publicly available GDSC datasets [51][52][53]. The parameter IC50 was also adopted in previous studies [54][55][56].…”
Section: Mutantmentioning
confidence: 99%
“…Ronnau et al, (2014) reported CBR3-AS1 as a potential biomarker for prostate cancer (Rönnau et al, 2014). Also, a recent study showed its activity in breast cancer drug sensitivity through MAPK Signal Pathway (Zhang et al, 2020). Although Zhang et al performed Adriamycin resistance breast cancer cells, we used fresh tissue to identify the potential lncRNA biomarker.…”
Section: Genementioning
confidence: 99%
“…On the other hand, due to the role of RAB6C gene (coding a centrosomal protein) in cell division (Kubiak et al, 2020), lcnRNA RAB6C-AS1 can be considered as a possible factor in the development of various cancers. Previously, the effect of carbonyl reductase gene (CBR3-AS1) has been shown in doxorubicin disposition of breast cancer (Xie et al, 2020), but there has been limited number of studies on the role of lcnRNA CBR3-AS1 (21q.22.2) in breast cancer (Zhang et al, 2020). However, the upregulation of CBR3-AS1 lcnRNA has been identified in prostate cancer and esophageal squamous carcinoma .…”
Section: Introductionmentioning
confidence: 99%